Stage 1 : Introductory Concepts for Explosive Power Training - Bauer, T.; Fuchs, D. (coachesinfo.com)
The concept of Explosive Power Training has been the focus of controversy among sport scientists and trainers in recent years. The research literature does not provide all the answers and practitioners report different levels of success using a variety of resistance modes and techniques. The Challenge of Human Muscle Power Enhancement for sport performance is based on the use of a variety of training approaches and it is generally agreed in the literature that some form of resistance exercise involving near maximal efforts will improve power output. However some sources question these methods which are open for discussion.